2002
DOI: 10.1071/mf01021
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interannual variations in diatom assemblages in Murray River connected wetlands in north-west Victoria, Australia

Abstract: Epipelic diatom assemblages collected from three wetlands connected to the Murray River displayed considerable variation in response to flooding and drying phases. Murray River water input usually generated diatom assemblages dominated by Aulacoseira species. After isolation, the diatom flora of two wetlands shifted to assemblages of small Fragilariaceae forms. Elevated nutrient levels corresponded with the appearance of eutraphentic taxa such as Cyclotella meneghiniana, Eolimna subminuscula, Luticola mutica a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 18 publications
2
61
1
Order By: Relevance
“…Salinity has previously been found to be the overriding environmental variable influencing Australian diatom communities and diatom-salinity (or -conductivity) relationships have been described (e.g. Hodgson et al 1997;Blinn and Bailey 2001;Gell et al 2002;Philibert et al 2006;Saunders et al 2007;Tibby et al 2007;Taukulis and John 2009). With the exception of Hodgson et al (1997) and Saunders et al (2007), none of these studies were conducted in coastal ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Salinity has previously been found to be the overriding environmental variable influencing Australian diatom communities and diatom-salinity (or -conductivity) relationships have been described (e.g. Hodgson et al 1997;Blinn and Bailey 2001;Gell et al 2002;Philibert et al 2006;Saunders et al 2007;Tibby et al 2007;Taukulis and John 2009). With the exception of Hodgson et al (1997) and Saunders et al (2007), none of these studies were conducted in coastal ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…For examples, Underwood et al (1998) and Zalat et al (2005) found a similar spatial pattern of diatom assemblages based on nutrient and salinity gradient along a small estuarine ecosystem in United Kingdom and in three lakes in Egypt along the Mediteranean coast, respectively. An investigation on Murray River connected wetlands in Australia (Gell et al 2002) also revealed salinity and nutrient control on the diatom taxa present, but demonstrated the dominance of salinity over nutrients on diatom assemblages once conductivity values exceed ~2 mS . cm -1 , as it is the case of some of our studied sites in some sampling occasions.…”
Section: Discussionmentioning
confidence: 99%
“…To date, periphyton were investigated and recently used as indicators of ecological conditions in wetlands mainly in some regions, such as the USA (Pan & Stevenson 1996, Pan et al 2000, Gaiser et al 2005, Wang et al 2006, Zheng & Stevenson 2006 and Australia (Gell et al 2002). In Italy, studies on benthic Diatoms are still (2) limited and mainly focused on the assessment of water quality of rivers (Dell'Uomo 1996, Ciutti et al 2003, Battegazzore et al 2004, Cappelletti et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…They found marked shifts in composition and the structure of diatom assemblages, increasing species richness and a replacement of halobiontic species by oligohalobic-indifferent forms, besides the vigorous growth of C. glomerata and E. intestinalis. Furthermore, Gell et al (2002) demonstrated the importance of salinity influence on the diatom community, and several conductivity-diatoms models have been developed for saline lakes to obtain quantitative estimates of past salinity.…”
Section: Effects Of Salinity Drop On Stream Functioningmentioning
confidence: 99%